2005
DOI: 10.1103/physrevd.71.055008
|View full text |Cite
|
Sign up to set email alerts
|

Neutrinos in anomaly mediated supersymmetry breaking withR-parity violation

Abstract: We show that a supersymmetric standard model exhibiting anomaly mediated supersymmetry breaking can generate naturally the observed neutrino mass spectrum as well mixings when we include bilinear R-parity violation interactions. In this model, one of the neutrinos gets its mass due to the tree level mixing with the neutralinos induced by the R-parity violating interactions while the other two neutrinos acquire their masses due to radiative corrections. One interesting feature of this scenario is that the light… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…The studies of the neutral Higgs sector have focused on the bilinear interactions alone [72,73] or a basis independent description in a one generation toy model. The study by De Campos et al, [110] discusses the mass spectrum of the MSSM with bilinear R parity violation in the scenario characterized by the conformal anomaly mediated supersymmetry breaking.…”
Section: Phenomenological Constraints On Bilinear R Parity Violationmentioning
confidence: 99%
“…The studies of the neutral Higgs sector have focused on the bilinear interactions alone [72,73] or a basis independent description in a one generation toy model. The study by De Campos et al, [110] discusses the mass spectrum of the MSSM with bilinear R parity violation in the scenario characterized by the conformal anomaly mediated supersymmetry breaking.…”
Section: Phenomenological Constraints On Bilinear R Parity Violationmentioning
confidence: 99%
“…1 → lll, τ ll, l bb, τ b b [97,98,99]. In our model, this scenario corresponds to large 3-cycles of the Exotic Instanton involved, i.e e −S E2 << 1, assuming string scale as M S 10 19 GeV.…”
Section: Neutrino Physicsmentioning
confidence: 83%
“…It has been shown that mAMSB with BRpV can account for the present neutrino data [21,22]. Like any SUSY BRpV neutrino mass model it predicts the normal hierarchy, since the neutrino masses becomes strongly hierarchical.…”
Section: Introductionmentioning
confidence: 82%
“…For further details we refer to [22]. The R-parity conserving soft terms will be assigned according to the minimal anomaly mediated scenario.…”
Section: Anomaly Mediated Supersymmetry With Brpvmentioning
confidence: 99%
See 1 more Smart Citation